Connective tissue growth factor regulates transition of primary bronchial fibroblasts to myofibroblasts in asthmatic subjects. (February 2018) - Wójcik-Pszczoła, Katarzyna; Jakieła, Bogdan; Plutecka, Hanna; Koczurkiewicz, Paulina; Madeja, Zbigniew; Michalik, Marta; Sanak, Marek
Graphical abstract: Highlights: CTGF contributes to fibroblasts-to-myofibroblasts transition in bronchial asthma. TGF-β1 -induced FMT in bronchial fibroblasts of asthmatics is enhanced by CTGF. CTGF silencing potently decreases TGF-β1 -induced FMT in bronchial fibroblasts. Abstract: Fibroblast to myofibroblast transition (FMT) contributes to bronchial wall remodelling in persistent asthma. Among other numerous factors involved, transforming growth factor type β (TGF-β) plays a pivotal role. Recently it has been demonstrated that connective tissue growth factor (CTGF), a matricellular protein, combines with TGF-β in the pathomechanism of many fibrotic disorders. However, it is not clear whether this interaction takes place in asthma as well. Primary cultures of human bronchial fibroblasts from asthmatic and non-asthmatic subjects were used to investigate the impact of CTGF and TGF-β1 on the fibroblast to myofibroblast transition. The combined activity of TGF-β1 and CTGF resulted in an average of 90% of FMT accomplished in cell lines derived from asthmatics. In this group FMT was highly dependent on the presence of CTGF produced by the cells, as shown by gene silencing experiments with the specific siRNA. Results support the important role of CTGF biosynthesis in the asthmatic bronchi amplifying FMT. This is evidenced by inhibition of TGF-β1 -induced FMT following CTGF silencing in asthmatic bronchial fibroblasts. CTGF is produced by fibroblasts and contributes to the FMT phenomenon in positive loop-back, inducing and boosting TGF-β1 triggered FMT. Thus, CTGF is a promising target for pharmacological intervention in secondary prevention of bronchial remodelling in asthma.